What do coordinators do? Mental health policy implementation as translation - Coralie Darcis; Sophie Thunus (Administrative Sciences, 2020)
Coordination is described as a widespread function emerging in relation to policy plans inducing collaboration between different sectors, organizations and professions. This paper suggests seeing the implementation phase as a translation process, one where the content of policy plans is reinvented primarily through discussion rather than linearly transferred from the political to the professional arena. It focuses on the function of coordinator with a view to examining how this function is performed and questions its influence on the local translation of both policy plans. The data collection was part of two research projects focusing on the reform of Belgian mental healthcare and the creation of care pathways for forensic patients, combining document analysis, interviews (n = 82) and observations (n = 58). The results highlight the inherent ambiguity of the coordinators' working environment, the socially-disputed nature of their function and define the coordinators as connection-makers who exert power over processes rather than people or structures. It demonstrates that coordinators influence the policy process by inducing discussions at meetings and the documents subsequently produced. In conclusion, this paper defines coordinators as process managers whose work largely consists of translating policy plans through event connectivity and contextualizing practices. Given the importance of translation in policy implementation, this paper calls for a reconsideration of policy evaluation as well as of the coordinators' recruitment and training procedures.
Keywords: 350; coordination; policy implementation; process management; improvisation; meetings and documents; mental healthcare policies; forensic policies